Metodologi Penelitian dan Etika Keguruan - Trisna Hartaty, Diva; Gunawan, Hadi (Jurnal Ilmu Pendidikan Islam, 2024)
Research methodology and teaching ethics are two important elements that complement each other in the context of education. Research conducted by teachers not only refers to strict scientific procedures, but must also pay attention to ethical aspects in teaching. This study aims to determine how research methodology and teaching ethics are. This study uses literature studies as the main method, where various relevant literature on educational research methodology and teaching ethics. The results of this study are that research methodology in education and teaching ethics are interrelated in creating an effective and meaningful learning process. The research methodology used in education must be chosen by considering the objectives and context of the research, while teaching ethics becomes the moral foundation for teachers in carrying out their duties. Teachers who adhere to the principles of teaching ethics can create a fair, inclusive learning environment that supports the development of student character